An electrochemical surface‐enhanced Raman spectroscopic study on nanorod‐structured lithium prepared by electrodeposition. (12th July 2016) - Tang, Shuai; Gu, Yu; Yi, Jun; Zeng, Zhicong; Ding, Song‐Yuan; Yan, Jia‐Wei; Wu, De‐Yin; Ren, Bin; Tian, Zhong‐Qun; Mao, Bing‐Wei
Abstract : Lithium is an s‐electron metal which is expected to support surface‐enhanced Raman scattering (SERS) effect. But the experimental investigation of the SERS effect of Li was reported once under high vacuum condition because of its extremely active surface chemistry. However, such investigations become increasingly important with stimulation by the active researches in lithium‐based batteries. In this paper, we present an electrochemical Raman spectroscopic study of electrochemically prepared Li surface combined with a simulation on the enhancement factor. Electrochemical roughening of Li foil surface and electrodeposition of Li on copper substrates are employed to prepare Li nanostructures. Only the nanorod arrays prepared by the electrodeposition on Cu in the electrolyte of LiPF6 –PC–H2 O or LiPF6 –EC–DMC–H2 O appear to be effective for obtaining the SERS effect. The spectra show two broad yet dominant bands at 720 and 1020 cm −1, which are considered to arise mainly from combined contribution by LiOH and LiF (720 cm −1 ) and LiF and Li2 CO3 (1020 cm −1 ) contained in the solid‐electrolyte interphase (SEI) layer on the nanorod‐structured Li surface. The enhancement factor is calculated for coupled nanorods of ca . 240 nm in diameter, which is about 30 and 7 times for 638 and 532‐nm excitations, respectively. Experimentally, the signals with 638‐nm laser excitation are two to three times stronger than those with 532‐nm laser excitation. The SERS effect of Li may provide a useful and convenient in‐situ method to follow the SEI evolution process in lithium‐based batteries without introducing extra SPR active metals that may have impact on the performance of the Li anode. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We obtain the surface enhanced Raman spectra of the solid‐ electrolyte interphase on the surface of nanorod‐structured lithium. The spectra show two broad bands at 720 and 1020 cm‐ 1 considered mainly from LiF, LiOH and Li2 CO3 in the SEI. The enhancement factor calculated is about 30 and 7 times for 638 and 532 nm excitations respectively.